Challenges And Constraints Affecting Female-Owned Rural Farm Businesses in Plateau State, Nigeria - Monday Tsaku Umbugadu; Abraham Meliga (International Journal of Rural and Regional Development, 2026)
This study examined the challenges and constraints affecting female-owned rural farm businesses in Plateau State, Nigeria. No prior study had conducted a comprehensive, quantitative, state-wide investigation covering all 17 local government areas (LGAs) of the state, and this study addressed that gap. The objectives were to identify the challenges faced by female-owned rural farm businesses, assess their relationship with business performance, and determine how strongly these challenges predicted performance outcomes. The study was conducted across all 17 LGAs of Plateau State, with 510 respondents selected using simple random, purposive, and snowball sampling techniques. A quantitative research design was adopted using structured questionnaires administered in English and local languages where necessary. Data was analyzed using the Statistical Package for the Social Sciences (SPSS) version 27.0, applying descriptive statistics, Pearson correlation, and multiple regression analyses. Financial exclusion, high input costs, poor road infrastructure, post-harvest storage gaps, and limited access to extension services were identified as the most reported challenges. Pearson correlation confirmed a significant negative relationship between challenges and business performance (r = -0.280, p = 0.000), and regression analysis further confirmed that challenges negatively predicted performance (B = -0.291, p = 0.000), while socio-demographic characteristics positively moderated outcomes. It was recommended that gender-targeted lending, rural storage facilities, road rehabilitation, expanded extension services, and conflict recovery frameworks be prioritized to support female-owned rural farm businesses in Plateau State.
Keywords: Challenges; and constraints; business performance; female-owned businesses; rural agriculture; rural farm businesses